KOMUNIKASI PERSUASIF DALAM KAMPANYE ANTI-KEKERASAN SEKSUAL OLEH KOMUNITAS LENTERA SINTAS INDONESIA - Dyah Nurul Maliki; Susanti Susanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
The number of cases of sexual violence that took place in this community environment was apparently unable to move the community to speak out. This condition makes early sexual education very necessary to increase the awareness of all parties to start a culture of reporting when experiencing or finding cases of sexual violence. The anti-sexual violence campaign that will be examined in this study is about the #MulaiBicara campaign formed by the Lentera Sintas Indonesia community. In this study, researchers will look at how the implementation of 10 persuasive communication techniques by William S. Howell. Data collection techniques using in-depth interviews and documentation. Data analysis was performed using the Miles and Huberman models. The researcher found that all of William S. Howell's persuasive communication techniques were implemented in the #Starting Talk campaign. William S. Howell's persuasive communication technique that is always carried out is the technique of the yes-response technique, the stimulated disinterest technique, and the technique of irritation. The researcher also found a dominant persuasive communication technique, where the implementation was carried out in a different way in the #MulaiBicara campaign, namely the reassurance technique.Keywords: Persuasive Communication, Campaign, Sexual Violence